Pencapaian Mashlahah Melalui Wakaf Asuransi Syariah - Safitri, Dara Ayu Okta (Jurnal Ilmiah Ekonomi Islam, 2023)
Islamic insurance waqf is an instrument that aims to protect and help each other among a number of people through investments in the form of assets and tabarru' which provide a return pattern to face certain risks or dangers through sharia-compliant contracts. And theoretically in an insurance institution can not be separated from the social spirit and helping each other. And currently, the difference of opinion about sharia insurance is still being debated among scholars. And this is a contemporary issue. Because the purpose of the tabarru contract is to create solidarity between insurance participants and insurance companies to help each other to people in need. So that it can achieve benefit to society. The concept of mashlahah in human life is the goal of maqhasid Syariah. The results of this study indicate that Islamic insurance waqf and Islamic maqhasid have the same goal, namely to realize the welfare of human life. And in this study used the library research method (library study) which was studied using books, journals and websites to achieve research objectives. This study aims to determine the effect of implementing waqf insurance on the achievement of community mashlahah